Pengembangan Perangkat Pembelajaran Matematika Berbasis Masalah dengan Pendekatan Saintifik Pada Pokok Bahasan Geometri untuk Peserta Didik SMA Kelas X - Rustiani S; Hafsyah Hafsyah; Putriyani S (Universitas Muhammadiyah Enrekang, 2018)
This study was a research and development which aimed at developing and producing mathematics learning tool for Geometry learning which was valid, reliable, objective, and practical.The product expected from this study was the learning tools on the topic of Geometry which was valid (R>85%), practical ( observe = 2) , and effective (THB = 85,7%, students activity > 80%, and positive response 98,7%). The product was consisted of 8 components, namely (1) Lesson plan; (2) Text book; (3) Worksheet; (4) Evaluation test of learning tools; (5) Observation sheet of students activity; (6) Observation sheet on implementation of learning tool; (7) questionnaire of students respons; and (8) validation sheet. The development process of authentic evaluation instrument used the modification of 4-D Model from Thiagarajan.The tried out was conducted at SMAN 1 Enrekang to grade X students. The result of the study revealed that the development of authentic evaluation instrument for Geometry learning which was valid, reliable, objective, and practical. Suggestion for this study are (1) other researchers who are interested in developing this study should learn the limitation of this study and (2) the development of authentic evaluation instrument for Geometry learning should also develop other subject materials to assist teachers in evaluating student’s based on their competence.